LOS JÓVENES UNIVERSITARIOS Y SUS PAUTAS DE CONSUMO Y DIFUSIÓN DE NOTICIAS SEGÚN LA TENDENCIA IDEOLÓGICA - Dra. Beatriz CATALINA-GARCÍA,Dr. Manuel MONTES VOZMEDIANO,Dr. Antonio GARCÍA JIMÉNEZ (Fonseca, Journal of Communication, 2023)
This paper aims to analyze to what extent and the ways in which the political positions of Spanish young people has influence on the consumption and access to news, with special interest in the digital point of view. This perspective is established in relation to aspects such as the media consulted, the credibility and the forms in which information is shared. In this sense, a survey self-administered for one month among 297 Communication students is conducted